A Key Component Determination on Forming Fairy Tofu from the Leaf of Premna Puberula (Verbenaceae) - Ming-Sheng Zhang, Meng-Na Shi, Bang-Rui Xu, Xiang-Dong Li, Ran Cao, Lin Chen (Journal of Applied Pharmaceutical Science)
A key component of Fairy Tofu from leaves of Premna puberula Pamp. was determined by immediate constituent analysis and prescription dismantlement analysis. The results showed that pectin in leaves of P. puberula was the key component as forming Fairy Tofu. It was because the highest component was pectin in Fairy Tofu except water, the pectin extracting directly from the leaves of P. puberula could be formed the jelly like Fairy Tofu, and the leaves which pectin was hydrolyzed by pectinase could not be made Fairy Tofu.
Keywords: Premna puberula Pamp, Fairy Tofu, Pectin, Enzyme treatment.